Neopaganism and the transformations of religiosity among American youth = Neopoganizm a przemiany religijności młodzieży amerykańskiej - Drozdowicz, Jarema (Przegla̜d religioznawczy, 2021)
This paper deals with the issue of the rise of neopagan movements and the changes occuring in the religiosity and spirituality of North American youth, It also tackles the problem of change in relation to the attitudes towards religion in general among adolescents in the United States and other parts of the world. The main objective is here to bring out the most significant aspects of this change and to contextualize the contemporary rise of neopaganism in terms of social and cultural factors. This step places the mentioned phenomenon in the context of the socio-cultural transformations which gave birth not just to modern neopagan movements but also New Age and other new forms of religiosity which gains popularity among the younger generations today.